Geomorphologic, circulation and dynamic analysis in a meandering tidal channel, Bahía Blanca Estuary - Angeles, Guillermo Raul (2003)
A meander of La Lista tidal channel (Bahia Blanca Estuary, Argentina) was selected in order to study the relationship between the geoforms that control the meandering channel evolution (mainly tidal flats and marshes) arid the dynamic and circulation characteristics of these channels. To achieve this goal a general survey was made in August 1999. The topographic characteristics of the channel and cross- section profiles from different sectors of the meander were compared with typical river profiles. Morphologic similarities between meander tidal channel cross-section (characterized by bidirectional flows) and meander river cross-section (characterized by unidirectional flows) were analysed. The largest velocities were measured during the ebb period (87 and 67 em S·l for U and V, respectively); during the flood period, the highest values registered were 53 and 33 em S·1 for U and V, respectively. Differences among the tidal current profiles along the meander were observed. Comparing the current velocity gradients in the different stations, the higher variations were observed during the flood period.